Co-delivering of oleuropein and lentisk oil in phospholipid vesicles as an effective approach to modulate oxidative stress, cytokine secretion and promote skin regeneration - Sklenarova, Renata; Allaw, Mohamad; Perra, Matteo; Castangia, Ines; Frankova, Jana; Luis Pedraz, Josè; Letizia Manca, Maria; Manconi, Maria (European journal of pharmaceutics and biopharmaceutics, 2023)
In this work oleuropein and lentisk oil have been co-loaded in different phospholipid vesicles (i.e., liposomes, transfersomes, hyalurosomes and hyalutransfersomes), to obtain a formulation capable of both inhibiting the production of different markers connected with inflammation and oxidative stress and promoting the skin repair. Liposomes were prepared using a mixture of phospholipids, oleuropein and lentisk oil. Tween 80, sodium hyaluronate or their combination have been added to the mixture to obtain transfersomes, hyalurosomes and hyalutransfersomes. Size, polydispersity index, surface charge and stability on storage was evaluated. The biocompatibility, anti-inflammatory activity and wound healing effect were tested using normal human dermal fibroblasts. Vesicles were small (mean diameter ∼ 130 nm) and homogeneously dispersed (polydispersity index ∼ 0.14), highly negatively charged (zeta potential 02053-64 mV) and capable of loading 20 mg/mL of oleuropein and 75 mg/mL of lentisk oil. The freeze-drying of dispersions with a cryoprotectant permitted to improve their stability on storage. The co-loading of oleuropein and lentisk oil in vesicles inhibited the overproduction of inflammatory markers, especially MMP-1 and IL-6, counteracted the oxidative stress induced in cells using hydrogen peroxide, and promoted the healing of a wounded area performed in vitro in a cell monolayer of fibroblasts. The proposed co-loading of oleuropein and lentisk oil in natural-based phospholipid vesicles may hold promising therapeutic value especially for the treatment of a wide variety of skin disorders.
Keywords: fosfolipidy; oxidační stres; liposomy; cytokiny; Cytokines; Liposomes; lidé; Oxidative Stress; Phospholipids; Wound Healing; Skin; kůže; Humans; hojení ran